Motivation for knowledge management approach and future prospects: A review of perspectives in Bangladeshi organisations - Habib, Laila; Mehzabin, Mehnaz Ahmed (Annals of Human Resource Management Research, 2024)
Purpose: Knowledge management is becoming an area of interest for striving towards extensive organisational development. The key to organisational development in the current business environment depends on how much knowledge is shared to accommodate the resources. The article aims to investigate the use of knowledge-sharing approaches by organisations in Bangladesh, where the concept is relatively new and explore the deficiencies and gaps in this area. Research Methodology: The study is purely qualitative. For this review article, 40 articles about knowledge sharing and management have been reviewed to develop an understanding of the concept of KM and its application in the context of MNEs in Bangladesh. Results: As knowledge management is a new concept in Bangladesh and other developing countries, there is limited study about KM and KS. It is therefore crucial to develop an understanding of the concept of having a strong position in the competitive business environment. Hence, the need to address the gaps, barriers and challenges of knowledge sharing and knowledge management extends beyond literature and proceeds to accommodate the concepts further extending towards research in this field. Contribution: With the emergence of the concept of knowledge management, organisations are becoming more aware of the need to encourage KS and address the limitations. It is important to develop innovative methods, and processes to bring about positive changes in organisational demography, practices and policies. Furthermore, better knowledge management will enhance the profitability and performance of organisations in countries like Bangladesh and other developing countries. Novelty: As the concept is relatively new in Bangladesh, it is possible to expand its scope further in different industrial contexts. It is also possible to explore the use of knowledge-sharing tools for organisational development.